Learning Styles, Gender and Academic Performance in Students in the Fundamentals of Economics Course (2023)
Acevedo Pierart, C. G., & Rocha Paves, F. (2011). Learning styles, gender and academic performance. Journal of Learning Styles, 4(8), 71-84.